2000
DOI: 10.1161/01.atv.20.4.1047
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Is a Strong but Nonspecific Risk Factor of Fatal Stroke in Elderly Persons

Abstract: Abstract-An elevated level of C-reactive protein is a strong predictor of cardiovascular events in elderly persons. Whether C-reactive protein has direct adverse vascular effects or is a marker of aspecific systemic inflammation remains to be determined. The aim of this study was to investigate the relation between C-reactive protein and the occurrence of fatal strokes in elderly persons. In the Leiden 85-Plus Study, a population-based prospective follow-up study, we studied the levels of C-reactive protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 21 publications
5
69
2
1
Order By: Relevance
“…To the best of our knowledge, this is the first prospective study to explore the joint associations of CRP and carotid IMT in incidence of ischemic stroke, although a case-control study published by CHS investigators demonstrated the interrelation of subclinical atherosclerosis and CRP in relation to coronary artery disease. 17 We confirmed prior observations that higher CRP is associated with future stroke [1][2][3][4] and extended prior findings to examine the independent roles of CRP and carotid atherosclerosis in relation to ischemic stroke. An independent association of CRP from carotid IMT in the risk of stroke suggests a hypothesis of an additional pathophysiological role for CRP to that of measurable atherosclerosis in relation to stroke.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first prospective study to explore the joint associations of CRP and carotid IMT in incidence of ischemic stroke, although a case-control study published by CHS investigators demonstrated the interrelation of subclinical atherosclerosis and CRP in relation to coronary artery disease. 17 We confirmed prior observations that higher CRP is associated with future stroke [1][2][3][4] and extended prior findings to examine the independent roles of CRP and carotid atherosclerosis in relation to ischemic stroke. An independent association of CRP from carotid IMT in the risk of stroke suggests a hypothesis of an additional pathophysiological role for CRP to that of measurable atherosclerosis in relation to stroke.…”
Section: Discussionsupporting
confidence: 83%
“…[1][2][3][4] Higher CRP is also associated with higher IMT, 5,6 although this has not been confirmed in all studies. 7,8 It is not clear whether CRP and carotid IMT each play an independent role in the pathogenesis of stroke.…”
mentioning
confidence: 88%
“…In the Physicians' Health Study of healthy middle-aged men and in the Women's Health Study of healthy postmenopausal women, total cholesterol and CRP both predict incident myocardial infarction, yet only CRP predicts incident stroke. 4,5 Almost identical data regarding CRP and thromboembolic stroke have now been presented in cross-sectional data from the National Health And Nutrition Examination Survey (NHANES) 7 as well as in two prospective cohorts, the Leiden 85-Plus Study 6 and the Framingham Heart Study. 8 In Framingham, for example, baseline CRP proved to be a strong linear predictor of incident stroke even after adjustment for other atherothrombotic risk factors, data that confirm the utility of CRP as an adjunct in the global prediction of cardiovascular risk.…”
Section: See P 2632mentioning
confidence: 99%
“…Accumulating evidence suggests that inflammation plays an important role in the development of cardiovascular and cerebrovascular disease [1,2]. Over the past few years has been stressed the role of inflammation in the pathophysiology of acute brain ischemia and how most inflammatory events are mediated by cytokines, small glycoproteins expressed by many cell types in response to acute cerebral ischemia [3,4].…”
Section: Introductionmentioning
confidence: 99%